Pengaruh Campuran Tepung Larva Lalat Tentara Hitam (Hermetia illucens) terhadap Performa Produksi dan Kualitas Telur Burung Puyuh (Coturnix coturnix japonica) - Hasna Safira Amnevi; Ramadhani Eka Putra; Rika Alfianny (UIN Sunan Gunung Djati Bandung, 2021)
Food of animal origin, which is generally relatively expensive. Animal proteins that are cheap enough for the public to buy include quail meat and eggs (Coturnix-coturnix japonica). Quail is one of the poultry that produces animal protein for humans because its body contains protein that comes from its food. Black Soldier Fly larvae (BSF) is one of the insects that can be used as animal feed because of its high protein and fat content. This study aimed to determine the effect of the mixture of BSF larvae meal with SP-22 commercial feed on the production performance and quality of quail eggs and determine which treatment produced similar performance to the reference treatment (treatment A). This study used 80 quail with ration formulations A (100% commercial feed (CF)), B (25% BSF + 75% CF), C (50% BSF + 50% CF), D (75% BSF + 25% CF), and E (100% BSF). The results showed that there were only significant differences in Feed Conversion Ratio (FCR), Production Egg, Haugh Unit (HU), Yolk Index (YI), and organoleptic (flavor, taste, and egg yolk color) and rations that produced similar performance to the reference treatment (treatment A) is treatment D.